A Simplified Procedure for the Preparation of 131I-Labelled Sulfobromophthalein. Its Applications to Liver Scanning - Suwanik, Romsai; Tubis, Manuel; Viranuvatti, Vikit; Limwongse, Kasem (Nuklearmedizin - NuclearMedicine, 1970)
A method of preparing 131I-labelled sulfobromophthalein is described. The method is simple and inexpensive. The labelled compound is of particular value where 99mTc-labelled preparations for liver scanning are too expensive or not readily available. It has been used as a liver scanning agent with satisfactory-results, revealing both morphological as well as functional abnormalities in various liver conditions in the same manner as 131I-labelled Rose Bengal.Its use in liver scanning has been extended to the visualization of the liver abscess cavity after intracavitary injection. The method has been used to observe the changes in size and configuration of the abscess cavity during its course of healing under medical treatment. Another extension of the work is the intraductal administration of the labelled compound viaa T-tube to demonstrate the dilatation of the biliary tract in cases of advanced opisthorchiasis.The application of the labelled compound to liver scanning is illustrated.